Airplane II : the sequel [videorecording (DVD)] - Bernstein, Elmer; Hazard, Dick (Widescreen DVD collection., 2017)
A faulty computer causes a passenger space shuttle to head straight for the Sun. Can Ted Striker save the day and get the shuttle back on track--again?